Dynamics of a Higher-Order Family of Iterative Methods - Plaza, S (Academic Press, 2011)
We study the dynamics of a higher-order family of iterative methods for solving non-linear equations. We show that these iterative root-finding methods are generally convergent when extracting radicals. We examine the Julia sets of these methods with particular polynomials. The examination takes place in the complex plane. © 2010 Elsevier Inc. All rights reserved.